Estimating probabilities of default of different firms and the statistical tests - Amir Ahmad Dar; N. Anuradha; Shahid Qadir (Journal of Global Entrepreneurship Research, 2019)
Abstract: The probability of default (PD) is the essential credit risks in the finance world. It provides an estimate of the likelihood that a borrower will be unable to meet its debt obligations. Purpose: This paper computes the probability of default (PD) of utilizing market-based data which outlines their convenience for monetary reconnaissance. There are numerous models that provide assistance to analyze credit risks, for example, the probability of default, migration risk, and loss gain default. Every one of these models is vital for estimating credit risk, however, the most imperative model is PD, i.e., employed in this paper. Design/methodology/approach: In this paper, the Black-Scholes Model for European Call Option (BSM-CO) is utilized to gauge the PD of the Jammu and Kashmir Bank, Bank of Baroda, Indian Overseas Bank, and Canara Bank. The information has been taken from a term of 5 years on a yearly premise from 2012 to 2016. This paper demonstrates how d2 in Black Scholes displayed help in assessing the PD of the various firms. Findings: The fundamental findings of this paper are whether there are any mean contrasts between the mean differences of PD between the organizations utilizing ANOVA and the Tukey strategy.
Keywords: 650; PD; BSM-CO; Merton model; ANOVA; Tukey method